Challenges of Algerian Folk Literature in the Context of Globalization Culture - difallah, Said; hammachi, hassina; belberki, fatima (El Omda in Linguistics and Discourse Analysis, 2022)
Algerian folk literature is an oral art that, in its entirety, constitutes the nation’s heritage and outlines its cultural identity. It evolves to adapt to the demands of renewal without detaching from its roots or denying its foundations. This has secured for it a unique position in affirming its rich content of noble values and virtuous behaviors—values that globalization has increasingly marginalized by distancing individuals from their past and distracting them with the attractions of Western modernity, often far removed from Islamic ethics. Through this research paper, we seek to address a set of key questions, including: To what extent does Algerian folk literature, in its various forms, contribute to the preservation and rooting of cultural heritage? How long can folk literature continue to withstand the pressures of globalization, both in the present and in the future?